EVALUATION OF USER EXPERIENCE (UX) HNI MOBILE USING THE THINK ALOUD METHOD - Revansa, Muhammad Dio; Angraini, Angraini; Ahsyar, Tengku Khairil; Syaifullah, Syaifullah (Informatika, Universitas Jenderal Soedirman, 2024)
User experience (UX) evaluation is important to determine the quality of a product or service. This research evaluates the UX of the HNI Mobile application using the think aloud method which asks users to express their thoughts while using the system. Involving 5 respondents who performed 10 task scenarios. The respondents' verbalization data, transcribed, and analyzed with NVIVO 12. The results obtained 5 main codes/themes of problems, namely profile editing, language features, member notifications, feature layout, and feature upgrades, which were visualized in a mind map. A retrospective probing technique was used to understand user difficulties. Although the main features functioned well, some respondents experienced difficulties in using the supporting features such as edit profile, change language, and access notifications. These findings provide input to improve the user experience of the HNI Mobile app in the future.